Perancangan Model Ontologi Domain Tanaman Upakara Hutan Yadnya Monkey Forest PadangTegal - I Kadek Dwika Pradnyana; I Putu Gede Hendra Suputra (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2025)
Upakara, which is frequently constructed from a variety of materials and given with symbolic roles and profound religious philosophical connotations, is an essential tool in Balinese Hindu religious events.